Virtue or Vice: The Nature of Loyalty. (4th July 2019) - Rutgers, Mark R.; Yang, Lijing
Abstract : This article aims to discuss the meaning of loyalty. Over the decades, authors have recognized loyalty ranging from an "ultimate value" to "immoral, " depending on the consequences linked to its impact. Three types of loyalty are distinguished here, according to the cause or object of loyalty at which it is directed. When discussing loyalty, a crucial question is of loyal to what or whom. However, a multiplicity of possible loyalties is at play in administrative practice, particularly in different cultural contexts. This article argues that the core of loyalty for civil servants lies in principled loyalty: it is more than an obligation or commitment; it involves reference to a moral sense of "good."